Prevention of Venous Thrombo-Embolism in Non-surgical Hospitalized Patients (Faculty of Medicine Universitas Indonesia, 2010)
Venous thromboembolism (VTE) is commonly found in hospitalized patients, considered as complication not only in surgical patients but also in medical patients. The vast majority of hospitalized patients with VTE or pulmonary embolism have not undergone any recent surgery. Several large randomized, double-blind, placebo controlled trials including MEDENOX, PREVENT and ARTEMIS have confirmed the efficacy and safety of VTE thromboprophylaxis for acutely ill medical inpatients. The American College of Chest Physicians (ACCP) Guidelines 2008 recommend a risk assessment at the time hospital admission for every medical patients and VTE prophylaxis using either anticoagulant medications or mechanical prevention should be applied for those who have high risk condition. Other studies showed that many cases of VTE in medical patients occur after hospital discharge, but still no clinical trials and current recommendation evaluating VTE prophylaxis for medical outpatients have been published yet. In this article, we attempt to review the literatures on importance of risk assessment and VTE prophylaxis for hospitalized medical patients. (Med J Indones 2010; 19:71-7)Keywords: venous thromboembolism, hospitalized patients, risk assessment, thromboprophylaxis